2015
DOI: 10.1016/j.antiviral.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in favipiravir (T-705) pharmacokinetics and biodistribution in a hamster model of viral hemorrhagic fever

Abstract: Favipiravir (T-705) is a new anti-influenza drug approved for human use in Japan and progressing through Phase 3 clinical trials in the U.S. In addition to its potent inhibitory effects against influenza virus infection, the compound has been shown to be broadly active against RNA viruses from 9 different families, including the Arenaviridae. Several members of the Arenaviridae family of viruses are significant human pathogens that cause viral hemorrhagic fever, a severe systemic syndrome where vascular leak i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
4
22
1
Order By: Relevance
“…A good penetration of favipiravir in lungs was observed with lung/plasma ratios ranging from 35 to 44% after repeated doses, consistent with its physicochemical properties. Lung exposure was also in accordance with previous studies 36 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A good penetration of favipiravir in lungs was observed with lung/plasma ratios ranging from 35 to 44% after repeated doses, consistent with its physicochemical properties. Lung exposure was also in accordance with previous studies 36 .…”
Section: Discussionsupporting
confidence: 92%
“…Favipiravir PK in our hamster model displayed a non-linear increase in plasma exposure between the doses as already reported in nonhuman primates 35 . The observed favipiravir concentration versus time profiles were in agreement with previous results of a PK study performed in 7-8 week-old hamsters orally treated with a single dose of 100mg/kg of favipiravir 36 . The maximum plasma drug concentration occurred at 0.5 h after oral administration, earlier than in humans, and then decreased rapidly in agreement with its short half-life 37 .…”
Section: Discussionsupporting
confidence: 91%
“…First, the studies were conducted in noninfected animals, and infection may alter the drug concentration. For instance, a decrease of the favipiravir concentration was observed in a hamster model of arenavirus hemorrhagic fever (31). Second, the criterion used to propose the dosing regimens was based on the comparison between the EC 50 observed in vitro and the free plasma concentration of favipiravir, which may not be the best marker of nucleoside analogue antiviral activity.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption will need to be verified by assessing drug pharmacokinetics during the course of the infection. In particular a study conducted in hamsters has suggested that infection with arenavirus led to lower favipiravir plasma and tissue concentration and that the impairment in pharmacokinetics increased with higher viral load levels (Gowen et al, 2015). Second the viral clearance rate, c, and the eclipse phase rate of transition, k, had to be fixed to ensure parameter identifiability.…”
Section: Discussionmentioning
confidence: 99%